2017
DOI: 10.1016/j.jss.2017.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Utilization and impact of adjuvant chemotherapy among patients with resected stage II colon cancer: a multi-institutional analysis

Abstract: Background The use of chemotherapy among patients with stage II colon cancer is controversial. We aimed to define the utilization and factors associated with the receipt of chemotherapy and the impact of chemotherapy on long-term prognosis among a large, multi-institutional cohort of patients. Materials and Methods We identified 876 patients who underwent resection for stage II colon cancer between 2004 and 2013 at one of 7 participating institutions. Overall (OS) and recurrence-free (RFS) survival time was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 31 publications
0
14
0
1
Order By: Relevance
“…Many strategies have been applied to reduce the rate of incisional SSIs, including the administration of intravenous antibiotics, careful intraoperative bowel manipulation and the use of wound protectors. These strategies have proven effective, although there are still many incisional SSIs that are not preventable [84] and a subset of patients with less controllable risk factors (patients who are immunocompromised or are diabetic, patients undergoing emergency surgery, especially those with bowel perforation where the surgical field is highly contaminated) [88 , 89] . The most represented pathogens in incisional SSIs are actually bowel bacteria, such as E. coli , P. aeruginosa and Enterococcus spp.…”
Section: Methodsmentioning
confidence: 99%
“…Many strategies have been applied to reduce the rate of incisional SSIs, including the administration of intravenous antibiotics, careful intraoperative bowel manipulation and the use of wound protectors. These strategies have proven effective, although there are still many incisional SSIs that are not preventable [84] and a subset of patients with less controllable risk factors (patients who are immunocompromised or are diabetic, patients undergoing emergency surgery, especially those with bowel perforation where the surgical field is highly contaminated) [88 , 89] . The most represented pathogens in incisional SSIs are actually bowel bacteria, such as E. coli , P. aeruginosa and Enterococcus spp.…”
Section: Methodsmentioning
confidence: 99%
“…During the past two decades, advances in chemotherapy protocols have drastically decreased the risk of cancer recurrence and improved overall survival time of patients with stages III and IV [ 3 8 ]. On the other hand, use of chemotherapy among patients with stage II colon cancer is controversial [ 9 , 10 ], as is the usefulness of adjuvant chemotherapy after surgery. Therefore, better prognostic markers are needed to improve the outcomes of patients with CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, correcting for tumor size showed no survival difference between stages II and III patients who received adjuvant chemotherapy. Stage II CRC patients without traditional high-risk features (pT4, bowel obstruction or perforation, positive resection margins/lymphovascular/perineural invasion, poorly differentiated histology or less than 12 lymph nodes resected) are generally observed on surveillance, although there is evidence that adjuvant chemotherapy may be beneficial ( 31 , 32 ). This study showed that tumors greater than 10cm are associated with worse outcomes.…”
Section: Discussionmentioning
confidence: 99%